Globalization and employment : is anxiety justified? - LEE, Eddy (1996)
Examines four sources of anxiety about the effects of globalization, viz: (1) the fear in industrialized countries that competition from newly industrialised countries will cause rising unemployment and falling relative wages among unskilled workers; (2) the fear in developing countries that liberalization will lead to job losses and rising wage inequality; (3) the fear that globalization of the labour market is leading to a race to the bottom with respect to wages and labour standards; and, (4) the fear that in the face of these new problems, globalization also implies a loss of national policy autonomy and governments becoming impotent.